Immigration, Naturalization, and the Future of Public Education - Ryuichi Tanaka; Lídia Farré; Francesc Ortega (Institute for the Study of Labor (IZA), 2014)
This paper analyzes the effects of immigration on the education system of the receiving country from a political economy perspective. Specifically, we extend the school-choice model by Epple and Romano (1996b) and Coen-Pirani (2011) by incorporating a subsidy to private schools, a distinguishing feature of Spain's education system. We calibrate the model to match key moments of Spain's economy and education system in year 2008, the end of a large episode of immigration. By means of simulations we evaluate the effects of immigration on the size and quality of Spain's public education. Our main findings are as follows. First, immigration will lead to a small increase in the size of public education in terms of enrollment. However, this increase in size masks an important composition effect. There is a large native flight away from public schools that is offset by the large inflow of immigrant children into public schools. Secondly, we predict a large reduction in the quality of public education, an 11 percent reduction in public spending per student. Our analysis suggests that these effects will unfold unevenly over time. While the changes in the size (and student composition) of public schools will take place promptly upon arrival of the immigrants, the reduction in funding will be more gradual and only fully take place once the immigrant population has been enfranchised. We also provide estimates separately for Spain's regions, which enjoy some autonomy in their education policies and experienced widely different levels of immigration.
Keywords: D7; F22; H52; H75; J61; I22; I24; 330; education; public school; immigration; naturalization